Ruoksat. A system for capturing, persisting and presenting the digital footprint of soccer knowledge and expertise - Sørensen, Kim-Edgar (Universitetet i Tromsø, 2013)
There are currently over 27 000 registered soccer teams in Norway. However, even with mandatory coaching licenses, there are still a vast variety of approaches to how training sessions should be planned and executed. Even in top-level professional soccer organizations, the planning of exercises involves a considerable amount of manual labor. The most common approaches include using old-fashioned pen and paper, or at best organizational tools like worksheets to plan exercises based on memory, word-to-mouth or vague guidelines. The exercises are presented to the players using sheets of paper along with verbal descriptions from the team coaches. The digital archiving possibilities are also limited, and knowledge related to the exercises, and exercise execution, is often not organized or persisted. This thesis designs, develops and evaluates a system for capturing, persisting and presenting expert coach knowledge in the form of exercises. The system is designed and developed with a particular focus on user interaction and user experience. The process is performed in close collaboration with coaches, medical staff and players from the elite level Norwegian soccer club Tromsø IL. The evaluation of the system is performed through a standard pairwise comparison between the implemented system and the solutions currently available to the assessors.